REASONS FOR Β-ADRENOBLOCKER USE IN ARTERIAL HYPERTENSION: ONE MORE TIME ABOUT PRO AND CONTRA - V. I. Makolkin (Столичная издательская компания, 2016)
Results of clinical trials devoted to β-adrenoblocker use in arterial hypertension (HT) are presented. Differences between β-adrenoblockers as well as β-adrenoblocker use in hypertensive patients with concomitant diseases are shown. The β-adrenoblocker position in up-to-date guidelines on HT diagnosis and treatment is discussed.